Intraocular Pressure Increases After Intraarticular Knee Injection With Triamcinolone but Not Hyaluronic Acid. Issue 7 (July 2018) - Taliaferro, Kevin; Crawford, Alexander; Jabara, Justin; Lynch, Jonathan; Jung, Edward; Zvirbulis, Raimonds; Banka, Trevor
Abstract: Background: Intraarticular steroid injections are a common first-line therapy for severe osteoarthritis, which affects an estimated 27 million people in the United States. Although topical, oral, intranasal, and inhalational steroids are known to increase intraocular pressure in some patients, the effect of intraarticular steroid injections on intraocular pressure has not been investigated, to the best of our knowledge. If elevated intraocular pressure is sustained for long periods of time or is of sufficient magnitude acutely, permanent loss of the visual field can occur. Questions/purposes: How does intraocular pressure change 1 week after an intraarticular knee injection either with triamcinolone acetonide or hyaluronic acid? Methods: A nonrandomized, nonblinded prospective cohort study was conducted at an outpatient, ambulatory orthopaedic clinic. This study compared intraocular pressure elevation before and 1 week after intraarticular knee injection of triamcinolone acetonide versus hyaluronic acid for management of primary osteoarthritis of the knee. Patients self-selected to be injected in their knee with either triamcinolone acetonide or hyaluronic acid before being informed of the study. The primary endpoint was intraocular pressure elevation of ≥ 7 mm Hg 1 week after injection. This cutoff is determined as the minimum significant pressure change in the ophthalmology literature recognized as an intermediate responder to steroids. Intraocular pressure was measured using a handheld Tono-Pen® applanation device. This device is frequently used in intraocular pressure measurement in clinical and research settings; 10 sequential measurements are obtained and averaged with a confidence interval. Only measurements with a 95% confidence interval were used. Over a 6-month period, a total of 96 patients were approached to enroll in the study. Sixty-two patients out of 96 approached (65%) agreed. Thirty-one (50%) were injected with triamcinolone and 31 (50%) were injected with hyaluronic acid. Patients with osteoarthritis of the knee who were suitable candidates for either a steroid injection or hyaluronic acid injection were included in the study. Exclusion criteria included previous glaucoma surgery, previous corneal injury precluding use of a Tono-Pen, current acute or chronic steroid use, and diagnosis of glaucoma other than primary open-angle. Patients with elevated intraocular pressure at the 1-week timepoint were invited to return at 1 month for repeat measurement; however, only five of nine (55.6%) were able to do so. The mean age of the total population was 64.1 ± 11.65 years. There were 46 (74%) women and 16 men. Patient in the hyaluronic acid injection group were younger than the triamcinolone group, 59.5 ± 11.7 versus 68.7 ± 9.7 years of age (p < 0.003). Results: The mean intraocular pressure increased by 2.79 mm Hg 1 week after treatment with triamcinolone, but it did not change among those patients treated with hyaluronic acid (2.79 ± 9.9 mm Hg versus -0.14 ± 2.96 mm Hg; mean difference 2.93 mm Hg; 95% confidence interval, -0.71 to 6.57 mm Hg; p = 0.12). More patients who received triamcinolone injections developed an increase in intraocular pressure > 7 mm than did those who received hyaluronic acid (29% [nine of 29] versus 0% [zero of 31]; p = 0.002). Of the nine patients who developed elevated intraocular pressure after a triamcinolone injection, five returned for reevaluation 1 month later, and four of them had pressures that remained elevated > 7 mm Hg from baseline. Conclusions: There appears to be an associated intraocular pressure elevation found in patients who have undergone a triamcinolone injection of the knee. Further larger scale randomized investigations are warranted to determine the longevity of this pressure elevation as well as long-term clinical implications, including optic nerve damage and visual field loss. Level of Evidence: Level II, therapeutic study.